Дослідження оптичних властивостей та керування збудженими станами циклометальованих комплексів платини(ІІ) - Shu Zhu; Шу Чжу (Харків : Харківський національний університет імені В. Н. Каразіна, 2024)
The optical properties of square-planar d8 platinum(II) complexes can be precisely controlled by regulating their structural and functional components. For instance, introducing the cyclometalated ligand with strong field characteristic will improve the singlet-triplet intersystem crossing, suppress the dark d-d excited state, and enhance the luminescent quantum efficiency. Ligands can tailor aggregation behavior of luminescent platinum complexes to aggregate via non-covalent bond interactions, such as π-π stacking and metal-metal interaction due to the planar configuration, yielding in deceased HOMO-LUMO band and appearance of absorption and emission bands at much longer wavelength.
Науковий керівник – Токарєв Віктор Володимирович, кандидат хімічних наук, старший викладач.
Keywords: NATURAL SCIENCES::Chemistry; Cyclometalated platinum(II) complexes; Excited state; Phosphorescence; Excimer; Luminescent probe